The Model of Turnover Intentions of Employees - Santoni, Alvia; Harahap, Muhammad Nusjirwan (International Review of Management and Marketing, 2018)
The purpose of this research to find out the influence of leadership, work environment, compensation, partial evaluation and jointly against job satisfaction and know the influence of leadership, work environment, compensation and job satisfaction as partial and jointly over turnover intentions of employees in the plastic industry of household appliances in the special capital region of Jakarta. The sample is taken using the proportionate random sampling. Data are descriptive analysis and explanatory analysis using sample of 260 respondents from 6226 population. The data analysis methods used are SEM (Structural Equation Modeling) with LISREL8.51 program. Based on the research results, leadership, working environment and compensation partially or jointly create significant positive effect on job satisfaction with the effect by 46% while the remaining 54% are influenced by other factors, but the most dominant partial is that compensation effect positively and significantly on job satisfaction. Leadership, work environment, compensation and job satisfaction partially or jointly significant effect on turnover intentions of employees with effect by 67% while the remaining 33% are influenced by other factors, but the most dominant influence in turnover intentions of employees is job satisfaction. The findings of this research are that for the turnover intention employees, especially the intention to move but for fear not getting better job (Y8) can be lowered if employees feel satisfied with the work itself (Y2) that is reinforced by work environment extern/ internal factors (X6) that in the form of selfish abstinence. Work satisfaction especially satisfied on the job himself can be increased if the company is able to improve the compensation for the employees which can be in the form of non-financial compensation (X9) especially a sense of security on the job as well as good leadership in the form of participative managerial capabilities (X2). Keywords: leadership, work environment, compensation, work satisfaction, turnover intentions JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7284